상요부탈장 - 이솔(Sol Lee); 장호진(Ho Jin Chang); 이이호(Lee Hoh Lee); 홍영란(Young Ran Hong); 정성우(Sung Woo Jung); 김승기(Seung Ki Kim); 정철운(Chul Woon Chung) (Annals of surgical treatment and research, 2010)
Lumbar hernia is an uncommon pathological defect of the abdominal wall. It presents difficulties in diagnosis and treatment because of the depth of the sac and the surrounding layers of muscle, fascia, and bone. It is an extrusion of intraperitoneal or extraperitoneal organs of the abdomen through a defect of the transversalis fascia. Inferior lumbar hernias are bordered by the iliac crest representing its base, limited by the external oblique muscle laterally, the latissimus dorsi medially, and the internal oblique muscle as its floor. Superior lumbar hernias are bordered by the 12th rib superiorly, quadratus lumborum muscle medially, and the internal oblique muscle laterally underneath the latissimus dorsi muscle. Diagnosis depends largely on the capacity for clinical suspicion, and confirmation is based on imaging tests. We report a case of an acquired primary lumbar hernia diagnosed by computed tomography, which was treated successfully at our institution. Lumbar hernia is an uncommon pathological defect of the abdominal wall. It presents difficulties in diagnosis and treatment because of the depth of the sac and the surrounding layers of muscle, fascia, and bone. It is an extrusion of intraperitoneal or extraperitoneal organs of the abdomen through a defect of the transversalis fascia. Inferior lumbar hernias are bordered by the iliac crest representing its base, limited by the external oblique muscle laterally, the latissimus dorsi medially, and the internal oblique muscle as its floor. Superior lumbar hernias are bordered by the 12th rib superiorly, quadratus lumborum muscle medially, and the internal oblique muscle laterally underneath the latissimus dorsi muscle. Diagnosis depends largely on the capacity for clinical suspicion, and confirmation is based on imaging tests. We report a case of an acquired primary lumbar hernia diagnosed by computed tomography, which was treated successfully at our institution. KCI Citation Count: 2